Focusing on Asthma and Chronic Obstructive Pulmonary Disease with COVID-19 - Bilun Gemicioglu; Hafize Uzun; Sermin Borekci; Ridvan Karaali; Sebuh Kurugoglu; Pınar Atukeren; Sabri Sirolu; Sinem Durmus; Ahmet Dirican; Mert Ahmet Kuskucu; Fehmi Tabak (Journal of Infection in Developing Countries, 2021)
Introduction: We aimed to evaluate clinical and laboratory findings of hospitalized asthma and chronic obstructive pulmonary disease (COPD) patients with COVID-19 and demonstrate that they have different symptoms and/or laboratory results and outcomes than COVID-19 patients with comorbidity (CoV-com) and without comorbidity (CoV-alone).